1) (1+cos u/1-cos u) - (1-cos u/1+cos u) = 4 cot u csc u

2) (csc x-1/csc x+1) = (cot^2 x/csc^2 x+2 csc x+1)

3) 9 csc^2θ - 7 cot^2θ = 2 csc^2θ +7

4) (cos u/1+tan u) - (sin u/1+cot u) = cos u - sin u

Printable View

- November 1st 2009, 03:11 PMla12establish the identity
1) (1+cos u/1-cos u) - (1-cos u/1+cos u) = 4 cot u csc u

2) (csc x-1/csc x+1) = (cot^2 x/csc^2 x+2 csc x+1)

3) 9 csc^2θ - 7 cot^2θ = 2 csc^2θ +7

4) (cos u/1+tan u) - (sin u/1+cot u) = cos u - sin u - November 1st 2009, 04:50 PMadkinsjr